A case of aphemia following non-dominant sub-insular stroke: unveiling the Foix-Chavany-Marie phenomenon. Issue 3 (4th May 2021) - Das, Saurav; Postman, Whitney; Haboubi, Michael A.; Akca, Ozan; Remmel, Kerri; Carter, Alexandre R.; Zazulia, Allyson
ABSTRACT: Aphemia refers to the clinical syndrome of inability to orally produce speech with intact comprehension and written expression. Aphemia has been primarily reported in dominant frontal lobe strokes resulting in apraxia of speech (AoS), and in Foix-Chavany-Marie (FCM) syndrome where bilateral opercular or sub-opercular lesions result in anarthria due to deafferentation of brainstem nuclei supplying the oro-facio-lingual and pharyngeal musculature. Aphemia is not reported in non-dominant sub-insular strokes. Here, we present a case of aphemia following non-dominant sub-insular stroke in a patient who had previously recovered from a homologous dominant sub-insular stroke without any apparent residual deficits. We discuss the accepted definitions, theories and controversies in the use of the terminology – aphemia, apraxia of speech (AoS), anarthria related to FCM syndrome, a concomitant pathology – unilateral upper motor neuron (UUMN) dysarthria, and their neuro-anatomical bases. We also highlight the importance of attributing localization value to sequential homologous lesions of the brain that can unveil symptoms due to a "loss of compensation phenomenon" that we propose be termed as "FCM phenomenon." These pathological mechanisms may alone or in certain combinations contribute to the clinical syndrome of aphemia included in the diagnostic approach proposed here. The distinction between these mechanisms requires serial careful neurological examination and detailed speech evaluation including in the recovery phase.